1984
DOI: 10.1007/bf00155676
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative stimulus/response function in human amblyopia

Abstract: Three parameters are essential to describe static accommodative behavior in a comprehensive, quantitative manner: the slope of the stimulus/response curve, the depth of focus, and the tonic response. These parameters were obtained in amblyopes, former amblyopes, strabismus without amblyopia, and normals. Results showed that the accommodative response in the amblyopic eye was characterized by a reduction in the slope of the stimulus/response curve and increased depth of focus. Similar abnormalities but of lesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
3

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 41 publications
3
32
0
3
Order By: Relevance
“…Several studies have directly shown that the DOF of an amblyopic eye is larger than that of its fellow nonamblyopic eye. 22,41,42 The sensory DOF hypothesis would predict that accommodative performance should be correlated with the magnitude of vision deficits. Studies have found that adults with unilateral amblyopia have both reduced contrast sensitivity and higher accommodative lags over the entire spatial frequency spectrum when viewing with their amblyopic eye.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have directly shown that the DOF of an amblyopic eye is larger than that of its fellow nonamblyopic eye. 22,41,42 The sensory DOF hypothesis would predict that accommodative performance should be correlated with the magnitude of vision deficits. Studies have found that adults with unilateral amblyopia have both reduced contrast sensitivity and higher accommodative lags over the entire spatial frequency spectrum when viewing with their amblyopic eye.…”
Section: Discussionmentioning
confidence: 99%
“…The binocular accommodative control via the 3rd nucleus may not be absolute. Amblyopes are liable to exhibit weaker accommodation in the amblyopic than in the normal eye [31][32][33]. Since the amblyopic eye has the greater depth of focus, it needs less accommodative power.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced accommodative performance could be attributed to a primary sensory loss over the retinal region as a result of prolonged, abnormal visual experience due to the presence of strabismus, resulting in abnormal binocular interactions and monocular contrast deprivation. [12][13][14][15] Reduced sensitivity to either a focused or …”
Section: Discussionmentioning
confidence: 98%